A method of multi-attribute assessment using ideal alternative: choosing an apartment with optimal indoor environment - Kalibatas, Darius; Zavadskas, Edmundas Kazimieras; Kalibatienė, Diana (International Journal of Strategic Property Management, 2012)
An indoor environment of each building depends on a number of criteria, like temperature, humidity, noise, etc. Therefore, multi-attribute decision making (MADM) methods are used to assess alternatives and to choice the rational one. In this paper we suggest to add a concept of ideal alternative into assessment using MADM, since it allows both to determine the optimal solution and the deviation of each alternative (an indoor environment of a building) from the optimal values, e.g. ideal alternative. Therefore, a method of multi-attribute assessment using ideal alternative (MAAIA) is formulated in this paper. It is applied for the MOORA method to assess an indoor environment of apartments in block houses situated in Naujoji Vilnia, Vilnius, Lithuania. Obtained results of the assessment show that the proposed method is useful for decision support and assessment of alternatives.First Publish Online: 2 Oct 2012